The Ups and Downs of Rattan Handicraft Industrial Centers in Tegalwangi Village 1973-2017 - Islamy, Vina Agustine; Yuliati, Dewi (History Department, Semarang State University and Historian Society of Indonesia, 2021)
Abstract: This article discusses the ups and downs of the rattan handicraft industrial centers in Tegalwangi Village in 1973-2017. This study outlines matters related to the rattan handicraft industry and the influence of the existence of the rattan handicraft industry on the socio-economic life of the residents of Tegalwangi Village. The writing of this study used a historical method consisting of four methods; which is: heuristic (source collection), which consist of primary and secondary sources, critical source, interpretation source, and historiography. Rattan handicraft products in Tegalwangi Village are the excellent commodity of Cirebon Regency. The ups and downs of the rattan handicraft industry can be seen from the ups and downs of the number of business units and laborers. Rattan handicraft industry has existed in Tegalwangi Village since the 1930s, which was first established by one of its residents named Semaun. The new rattan handicraft industry began to develop in the 1970s, marked by the establishment of the Tegalwangi rattan handicraft coop in 1973, which also influenced the development of rattan handicraft industry centers in this village.Ã‚Â Abstrak: Artikel ini mengkaji tentang pasang surut sentra industri kerajinanrotan di DesaTegalwangi tahun 1973-2017. Penelitian ini menguraikan hal-hal yang berkaitan dengan industri kerajinan rotan dan pengaruh keberadaan industri kerajinan rotan bagi kehidupan social ekonomi penduduk Desa Tegalwangi. Penelitian ini menggunakan metode sejarah kritis yang mencakup empat langkah, heuristik (pengumpulan sumber) yang terdiri dari sumber primer dan sekunder, kritik sumber, dan historiografi. Produk industri kerajinan rotan di Desa Tegalwangi merupakan komoditi unggulan Kabupaten Cirebon. Pasang surut industri kerajinan rotan dapat dilihat dari naik-turunnya jumlah unit usaha dan tenaga kerja. Industri kerajinan rotan sudah ada di Desa Tegalwangi sejak tahun 1930-an yang didirikan pertama kali oleh salah satu penduduknya yang bernama Semaun. Industri kerajinan rotan baru mulai berkembang sejak tahun 1970-an ditandai dengan berdirinya Koperasi kerajinan rotan Tegalwangi pada tahun 1973 yang turut mempengarui perkembangan sentra industri kerajinan rotan di desa ini.Ã‚Â